The Role Of Islamic Religious Education Teachers In The Forming Of Pancasila Students Profile Dimensions Of Noble Character - Endrik Mas Yulaidi; Ricky Ulanda Kostriono; Wildan Irwahyudi; Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2022)
In an era of increasingly rapid technological development, many people are addicted to Gadgets. It can be seen from the number of users of gadgets (smartphones) globally increasing from year to year. The high use of excessive or inappropriate gadgets has an influence on the personality and character of the community. It can be seen from the many cases that reflect the bad character of Indonesian society, such as corruption, cyberbullying, brawls between lessons, and other cases. The purpose of this study was to determine the role of Islamic religious teachers in the character formation of Pancasila student profile dimensions of noble character in the Laboratory Primary School of UM Blitar. This study used a qualitative descriptive research design with a case study approach. The data collection techniques used in this study were interviews and documentation studies. This research was conducted at Laboratory Primary School UM Blitar, with the Islamic religious teacher as the key informant. The results showed that Islamic religious teachers are one of the pioneers in the success and formation of student personality, because they play an important role as sponsors or imitators in the implementation of personality formation in schools.  The contribution of Islamic education teachers in shaping the character of students is empowerment, exemplary, intervention, integrated, sekrening. Keywords: Character education, Islamic Religious Education, Pancasila students, Teacher’s Role.